Relationship of Body Mass Index and Haemoglobin with Cardiorespiration Endurane in Female College Students - Astuti, Nadia Ayu Kusuma; Faridah, Faridah; Fatimawati, Iis; Kertapati, Yoga (Universitas Islam Lamongan, 2020)
Cardiorespiratory endurance is the maximum capacity of using oxygen which can be influenced by Hb and BMI levels, so it does not get tired easily after doing activities. Students tend to have unbalanced Hb and BMI. This study aims to determine the relationship of BMI and hemoglobin levels with cardiorespiratory endurance in female college students.A literature review searched three database (Google Scholar, Pro Quest, and National Journal) that use cross-sectional or quasi-experimental designs published after 2010. The prism checklist is used as a guide to assess the feasibility of studies. The research findings were carried out by tabulating data and narrative analysis. Found 8 journals that met the inclusion criteria based on two broad that affected cardiorespiratory endurance, BMI (n=3), Hb (n=5). Most of these studies use cross-sectional or quasi-experimental designs. The average number of respondents of the study was more than 50 people for the study of the relationship of hemoglobin and body mass index with cardiorespiratory endurance in female college students.The research examined in this article shows that BMI and Hb are associated with cardiorespiratory endurance in female college students. This can be used as nurses to provide education about the importance of maintaining a balance of BMI and hemoglobin levels in increasing cardiorespiratory endurance so that they can perform physical activity maximally.Â